Phase formation in selected surface-roughened plasma-nitrided 304 austenite stainless steel - Gajendra Prasad Singh et al (Science and Technology of Advanced Materials, 2008)
Direct current (DC) glow discharge plasma nitriding was carried out on three selected surface-roughened AISI 304 stainless steel samples at 833 K under 4 mbar pressures for 24 h in the presence of N2:H2 gas mixtures of 50 : 50 ratios. After plasma nitriding, the phase formation, case depth, surface roughness, and microhardness of a plasma-nitrided layer were evaluated by glancing angle x-ray diffractogram, optical microscope, stylus profilometer, and Vickers microhardness tester techniques. The case depth, surface hardness, and phase formation variations were observed with a variation in initial surface roughness. The diffraction patterns of the plasma-nitrided samples showed the modified intensities of the α and γ phases along with those of the CrN, Fe4N, and Fe3N phases. Hardness and case depth variations were observed with a variation in surface roughness. A maximum hardness of 1058 Hv and a case depth of 95 μm were achieved in least surface-roughened samples.